Field Cancerization - A Case Report - K Sham Kishore; K Prashanth Shenai; Laxmikanth Chatra (Wolters Kluwer Medknow Publications, 2006)
Field cancerization was first described in 1953 as histologically altered epithelium surrounding tumor samples taken from the upper aerodigestive tract. Since then, the term has been used to describe multiple patches of premalignant disease, a higher than expected prevalence of multiple local second primary tumors and the presence of synchronous distant tumors within the upper aerodigestive tract. We report one such case of field cancerization in a 70-year-old male patient